Strategic Conflict Management? A Study of Workplace Dispute Resolution in Wales. (March 2020) - Nash, David; Hann, Deborah
In this article, the authors examine the relationship between organizational strategy and the approach taken to conflict management using a large-scale survey of companies in Wales, a constituent part of the United Kingdom. They focus on conflicts among employees, an under-researched form of conflict, to examine which types of organizations adopt a more strategic approach to conflict management that aligns with broader HR objectives. They find that organizations with a unitarist, and often anti-union, orientation are more likely to make strategic choices about how they address conflict. Equally, the authors argue that some evidence suggests that organizations that take high-road approaches to HR are more likely to take an intentional approach to how they address conflict.